Vertical measurements of roadside air pollutants using a drone - Lee, Suhyeon; Hwang, Hyemin; Lee, Jae Young (Atmospheric Pollution Research, 2022)
In this study, we vertically measured concentrations of PM2.5, black carbon and ozone using a drone in a high-polluted area surrounded by highways, general road and high-rise apartments, from October 2021 to April 2022 in South Korea. We found that the concentration of PM2.5 and black carbon showed minor concentration changes vertically up to 70 m from the ground, and decreased with height over 70 m. This is due to the limited air circulation due to the 50-m-tall apartment buildings. The O3 concentration was increased with height up to 30 m above the surface and increased slowly thereafter. This is due to the O3 titration by NO near the surface to form NO2 and to turn O3 into O2. In addition, we analyzed the effect of wind direction on the pollutant concentration of the measurement site near a road where a sound barrier is located in-between. We found no appreciable increase in the pollutant concentration when wind is flowing from the nearby road. This may be attributable to the sound barrier that is blocking the direct pathway from the road and the measurement site.